INFLUENCE CULTURE ORGANIZATION , HR COMPETENCE AND MASTERY TECHNOLOGY AGAINST EMPLOYEE PERFORMANCE POLYTECHNIC CRUISE SHOVE - I Made Mariasa; Amiruddin Matutu; Hurip Pratomo (Jurnal Ekonomi, 2023)
Study This based on assumptions that performance optimal employee can influenced by culture the organization itself . suitability between culture organization with values shared by each _ employee will raises satisfaction service will performance from something organization , so matter This expected will the more push employee to stay productive and creative in increase performance in organization and career in period long . Study This implemented using _ procedure study descriptive inferential to test connection variable free to variable bound . Variable freedom is culture Organization , Competence Officer , Mastery Technology , meanwhile variable bound is employee performance . Then processed and analyzed to see influence variable free to variable bound using path analysis. Obtained data Then will used to describe characteristics from population based on predefined variable . _ The result is there influence positive and significant Culture Organization to Mastery Technology Employee Polytechnic Cruise shove .